1992
DOI: 10.1099/0022-1317-73-1-139
|View full text |Cite
|
Sign up to set email alerts
|

Translational modulation in hepatitis B virus preS-S open reading frame expression

Abstract: A series of hepatitis B virus open reading frame (ORF)preS-S variants, including mutants in which the relative order of the in-frame start codons (AUG1, AUG2 and AUG3) and nearby sequences had been altered, was expressed both in vivo (in HepG2 hepatoblastoma cells) and in vitro (by T7 promoter-driven transcription followed by translation in a rabbit reticulocyte lysate). The ratio of the synthesis of the large, middle (M) and major (S) proteins or their chimeric counterparts was analysed to study the translati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…Another work demonstrated that, in HepG2 cells, N-terminal myristylation can block secretion of HBsAg even in the absence of any preS sequence (Prange et aI., 1991). In a previous report, we described a chimeric L protein mutant lacking the preS1 N-terminal sequence and still being substantially retained (Gallina et al, 1992). Here, we re-examine this issue, analysing a wider series of mutations in the preS region for their effects on envelope protein secretion.…”
Section: Intracellular Retention Of Hepatitis B Virus Surface Proteinmentioning
confidence: 99%
See 4 more Smart Citations
“…Another work demonstrated that, in HepG2 cells, N-terminal myristylation can block secretion of HBsAg even in the absence of any preS sequence (Prange et aI., 1991). In a previous report, we described a chimeric L protein mutant lacking the preS1 N-terminal sequence and still being substantially retained (Gallina et al, 1992). Here, we re-examine this issue, analysing a wider series of mutations in the preS region for their effects on envelope protein secretion.…”
Section: Intracellular Retention Of Hepatitis B Virus Surface Proteinmentioning
confidence: 99%
“…3, pRPAUG1.3ayw, pRPAUGI1.3adw2 and pRPpreS2A. Mutants AUG2.2.3, AUG1.3ayw and AUG1.3adw2 have been described previously (Gallina et al, 1992). Plasmids pRPpreS1A and pRPpreS2A express Y-terminally deleted versions of ORF preS-S. Mutant preS1A fuses a strong context AUG (Kozak, 1989) to preS1 codon 19 (ayw), thus eliminating codons 1 to 18 of the ORF.…”
Section: Intracellular Retention Of Hepatitis B Virus Surface Proteinmentioning
confidence: 99%
See 3 more Smart Citations